DESIGN A FEARLESS (FIRE SUPPRESSION AND SMART ALERT SYSTEM) ON GAS LEAKS - Rachman, Lindra Aulia; Hasbullah, Hasbullah (Journal of Industrial Engineering & Management Research, 2022)
In the natural gas management industry, gas leakage is a matter that must be considered. This is because if the leak is not handled immediately it will result in incidents and even work accidents that can lead to fatalities. To avoid gas leaks that can cause work accidents, a gas detector is used in the process to detect gas leaks from the start so that operators can find out if there is a gas leak. However, in the process, most of the gas detector equipment in the field experienced some damage which caused no gas leak to be detected and along with the development of gas detector detection system technology, its function could be upgraded to detect and extinguish fires caused by gas leaks. Taking these aspects into account, the purpose of this research is to design an automatic leak detection and fire extinguishing system called FEARLESS. The method used is a case study methodology and applied. From the data obtained in the field, it was found that there were 4 gas detector disturbances in 2019 and 5 times in 2020 which resulted in no detection of gas leaks when the detector was disturbed, as well as 34 gas leaks in 2019 and 42 times in 2020.